2021
DOI: 10.1038/s41598-021-93523-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of illuminance and correlated color temperature of indoor light on emotion perception

Abstract: The acute non-image forming (NIF) effects of daytime light on momentary mood had been-although not always-established in the current literature. It still remains largely unknown whether short-time light exposure would modulate emotion perception in healthy adults. The current study (N = 48) was conducted to explore the effects of illuminance (100 lx vs. 1000 lx at eye level) and correlated color temperature (CCT, 2700 K vs. 6500 K) on explicit and implicit emotion perception that was assessed with emotional fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…For instance, 1500 lx vs. 150 lx and 372 lx vs. 40 lx were employed in these two studies [ 35 , 36 ], respectively, while 1000 lx vs. 100 lx was employed in the current study. The effect of illuminance on satisfaction with light was scarcely investigated [ 19 , 30 ], while previous studies had occasionally reported significant effects of bright versus dim illuminance on state self-control [ 29 , 35 , 40 , 41 , 42 ] and mood [ 16 , 59 , 64 , 65 , 66 ]. Again, the differences in light manipulation make it difficult to directly compare the findings of previous studies and the current one.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 1500 lx vs. 150 lx and 372 lx vs. 40 lx were employed in these two studies [ 35 , 36 ], respectively, while 1000 lx vs. 100 lx was employed in the current study. The effect of illuminance on satisfaction with light was scarcely investigated [ 19 , 30 ], while previous studies had occasionally reported significant effects of bright versus dim illuminance on state self-control [ 29 , 35 , 40 , 41 , 42 ] and mood [ 16 , 59 , 64 , 65 , 66 ]. Again, the differences in light manipulation make it difficult to directly compare the findings of previous studies and the current one.…”
Section: Discussionmentioning
confidence: 99%
“…These suggest that children exhibited more engaged or joint attention, responses, and decision or desire to choose between or among objects manifested verbal or non-verbal movements in dyadic interactions when there were longer hours from sunrise to sunset and increased exposure to natural light source inside the classrooms. Through modulating circadian rhythm and sleep and activating emotion-processing brain regions, and suppression of melatonin production, UV light, illuminance, daytime light have been investigated focusing on its potential non-image forming indirect or direct regulating effects to mood or behavior 9,47,48 . Among children, these light-related indicators have been studied investigating its effects to or associations with physical activities, sedentary behaviors, socialization skills, cognitive abilities, attitudes, and energy levels in classroom settings.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, red light can be used to reduce daytime sleep inertia and improve short-term performance [ 15 , 16 ]. In addition, some findings highlighted the role of CCT in regulating instant emotion perception and showed lower CCT significantly decreased negative response bias in the face judgment tasks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%